2022
DOI: 10.1111/ecc.13752
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Frailty Scale can indicate prognosis and care requirements on discharge in oncology and haemato‐oncology inpatients: A cohort study

Abstract: Objectives: Routinely used performance status scales, assessing patients' suitability for cancer treatment, have limited ability to account for multimorbidity, frailty and cognition. The Clinical Frailty Scale (CFS) is a suggested alternative, but research detailing its use in oncology is limited. This study aims to evaluate if CFS is associated with prognosis and care needs on discharge in oncology inpatients.Methods: We evaluated a large, single-centre cohort study in this research. CFS was recorded for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Side 2 af 10 Clinical Frailty Scale (CFS) er et screeningsvaerktøj, der i tiltagende grad anvendes til vurdering af skrøbelighed hos aeldre patienter generelt, og CFS findes ligeledes i en dansk valideret udgave [17]. CFS scores på en skala fra 0 til 9 baseret på et klinisk skøn, hvor en score på ≥ 5 definerer skrøbelighed [18]. CFS er endnu kun sparsomt anvendt inden for onkogeriatrisk forskning.…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
See 1 more Smart Citation
“…Side 2 af 10 Clinical Frailty Scale (CFS) er et screeningsvaerktøj, der i tiltagende grad anvendes til vurdering af skrøbelighed hos aeldre patienter generelt, og CFS findes ligeledes i en dansk valideret udgave [17]. CFS scores på en skala fra 0 til 9 baseret på et klinisk skøn, hvor en score på ≥ 5 definerer skrøbelighed [18]. CFS er endnu kun sparsomt anvendt inden for onkogeriatrisk forskning.…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
“…CFS er endnu kun sparsomt anvendt inden for onkogeriatrisk forskning. I et kohortestudie har man påvist en association mellem skrøbelighed fundet ved CFS og et øget plejebehov ved udskrivelse samt øget dødelighed [18]. Der foreligger endnu ikke publicerede danske onkogeriatriske studier, hvor CFS anvendes.…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
“…Although international guidance exists recommending that frailty is assessed in older adults being considered for chemotherapy [28], this is not routine in the UK. However, the Rockwood Clinical Frailty Scale (CFS) [29] has been increasingly used to identify frail patients who may benefit from the input of specialist geriatric or oncogeriatric services in specific geographic regions [30,31]. The upcoming national guidance from the JCCO may further support the more widespread use of frailty assessments and development of pathways for specialist input within the UK.…”
Section: Geriatric Oncology In the Uk: Current Practicementioning
confidence: 99%
“…Stoppelenburg et al showed that the Surprise Question predicts death in hospitalised patients with cancer reasonably well and can help to initiate palliative care earlier (Stoppelenburg et al, 2022). Another tool is the Clinical Frailty Scale (CFS), although still limited used in oncology, Welford et al showed that in adult oncology inpatients, the CFS is associated with prognosis and care needs on discharge and may help predict prognosis in adult oncology inpatients (Welford et al, 2022). Also, awareness of patients with incurable cancer and their relatives is an important issue.…”
Section: How Can We Overcome These Barriers?mentioning
confidence: 99%
“…One tool for identify patients with potential palliative care needs is the Surprise Question “Would I be surprised if this patient died in the next 12 months?” Stoppelenburg et al showed that the Surprise Question predicts death in hospitalised patients with cancer reasonably well and can help to initiate palliative care earlier (Stoppelenburg et al, 2022). Another tool is the Clinical Frailty Scale (CFS), although still limited used in oncology, Welford et al showed that in adult oncology inpatients, the CFS is associated with prognosis and care needs on discharge and may help predict prognosis in adult oncology inpatients (Welford et al, 2022).…”
mentioning
confidence: 99%